Port Efficiency and Supply Chain Integration in Archipelagic Nations: A Case Study of Indonesian Hub Port Development Strategy - Alamsyah, Jaya (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STIP Jakarta, 2025)
This study investigates port efficiency optimization and maritime supply chain integration within archipelagic contexts, focusing on Indonesia's strategic hub port development initiatives. The research examines operational challenges including berth utilization, cargo handling efficiency, intermodal connectivity, and hinterland distribution networks across major Indonesian ports. Using data envelopment analysis and stakeholder interviews with port operators, shipping lines, and logistics providers, the study evaluates factors affecting port competitiveness in Southeast Asian maritime trade. The research analyzes how geographical dispersion, infrastructure limitations, and regulatory frameworks impact port performance and supply chain effectiveness. Findings offer strategic recommendations for enhancing port operations, improving connectivity between islands, and strengthening Indonesia's position in regional maritime logistics networks through integrated port development policies.